Characteristics of the Endoderm: Embryonic and Extraembryonic in Mouse - Mary Familari (The Scientific World Journal)
In mouse, four endodermal lineages are generated during the period from the late blastocyst to the end of gastrulation. The characteristics of each lineage and the proposed genetic cascades involved in their formation are reviewed. In addition, a list of the current markers used to identify these lineages in vivo and in vitro is presented.